Research on the Impact of Marine Environment on ICPT Transmission Efficiency - Da Li; Wei Gao; Xusheng Wu; Jianxin Gao; Shenqin Yang (International Journal of Antennas and Propagation)
ICPT is one of the most influential solutions in the field of wireless power transmission, but it is also very susceptible to the working environment. The complicated marine environment has a great influence on the performance of ICPT. In the deep-sea high-pressure environment, due to the piezomagnetic effect, the magnetic core in the coupling structure will suddenly change the permeability, and the coupling coefficient, self-inductance, and other parameters will also change accordingly. At the same time, changes in ocean currents in the ocean will cause the ICPT coils to be misaligned, thereby affecting the magnetic field distribution between the coils and the transmission efficiency of the system. In order to provide theoretical support for optimum design of ICPT system in ocean environment, the influence of core performance changes and ICPT coil misalignment on system transmission efficiency is studied.